EFFECT OF RESPIRABLE SUSPENDED PARTICULATE MATTER IN URBAN AMBIENT AIR ON HEALTH OF TRAFFIC POLICEMEN - RITA SINGH; MASTAN SINGH; RAJIV GARG; SM NATU (International Journal of Pharma and Bio Sciences, 2013)
Vehicular exhaust mainly consisting particulate matter sometimes called black carbon pollution is a mixture of solid and liquid components that form tiny particles that float in the air as a result of combustion of fuel. The aim of this study is to evaluate the effect of respirable suspended particulate matter (RSPM/PM10) on the automated count (WBC, TLC, DLC, ESR) and lipid profile (S. Cholesterol, HDL Cholesterol, LDL and S. Triglycerides). Sixty two traffic policemen were enrolled in the study group. By comparing the groups the mean value of total leukocyte count and platelets are not statistically significant change. But neutrophils, lymphocytes, eosinophils, ESR, S. Cholesterol, HDL Cholesterol, LDL and S. Triglycerides were found to be statistically significant (p<0.05). CRP was found positive in 48% of the study group. Our study infers that vehicular exhaust which includes respirable suspended particulate matter (RSPM/PM10) may affect automated blood count and lipid profile.